Breaking out of silos: Nexus thinking for natural resource management in Nepal - Phuyal, Surendra; Koirala, Sanju (CGIAR, 2024)
A workshop for policy makers in Nepal, supported by NEXUS Gains, encouraged discussion on developing a nexus approach that could improve the integrated management of water, energy, land, biodiversity, and forests nationwide